2014
DOI: 10.1016/j.ydbio.2014.09.023
|View full text |Cite
|
Sign up to set email alerts
|

CDC6 controls dynamics of the first embryonic M-phase entry and progression via CDK1 inhibition

Abstract: CDC6 is essential for S-phase to initiate DNA replication. It also regulates M-phase exit by inhibiting the activity of the major M-phase protein kinase CDK1. Here we show that addition of recombinant CDC6 to Xenopus embryo cycling extract delays the M-phase entry and inhibits CDK1 during the whole M-phase. Down regulation of endogenous CDC6 accelerates the M-phase entry, abolishes the initial slow and progressive phase of histone H1 kinase activation and increases the level of CDK1 activity during the M-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 21 publications
1
28
1
Order By: Relevance
“…Previously, we have shown that CDC6, acting as CDK1 inhibitor, regulates the timing and amplitude of CDK1 activity during the M-phase (El Dika et al, 2014a). However, we did not distinguish whether CDC6 inhibits CDK1/cyclin A, CDK1/cyclin B, or both.…”
Section: Cdc6 Regulates the Timing Of M-phase Progression Through Thecontrasting
confidence: 66%
See 1 more Smart Citation
“…Previously, we have shown that CDC6, acting as CDK1 inhibitor, regulates the timing and amplitude of CDK1 activity during the M-phase (El Dika et al, 2014a). However, we did not distinguish whether CDC6 inhibits CDK1/cyclin A, CDK1/cyclin B, or both.…”
Section: Cdc6 Regulates the Timing Of M-phase Progression Through Thecontrasting
confidence: 66%
“…Cyclin B accumulation to a threshold level is necessary to trigger the M-phase entry. However, as we previously showed, the CDC6-dependent mechanism controls in parallel the timing of the mitotic entry through the regulation of the dynamics of CDK1 activation (El Dika et al, 2014a). CDC6 allows setting the correct timing of M-phase entry, and controls the level of CDK1 activity in cooperation with the continuously increasing level of cyclin B.…”
Section: Discussionmentioning
confidence: 78%
“…As a consequence, oocytes enter a replicative interphase-like stage. This process involves the direct interaction between Cdc6 and Cdk1-Cyclin-B, a mechanism already known to contribute to exit from M-phase in Xenopus extracts, yeast and human cells (Archambault et al, 2003;Calzada et al, 2001;El Dika et al, 2014;Elsasser et al, 1996;Perkins et al, 2001;Weinreich et al, 2001). Interestingly, Cdc6 specifically associates with Cyclin B2 and Cdk1 in highmolecular-mass complexes, which are distinct from the canonical dimeric Cdk1-Cyclin-B complexes (De Smedt et al, 2002).…”
Section: Cip1mentioning
confidence: 98%
“…Interestingly, Cdc6 can inhibit Cdk1 during the G2/M transition (Archambault et al, 2003;Calzada et al, 2001;Clay-Farrace et al, 2003;El Dika et al, 2014;Elsasser et al, 1996;Murakami et al, 2002;Oehlmann et al, 2004). If such effect were to operate in oocytes, deregulation of Cdc6 accumulation is expected to disturb meiotic divisions.…”
Section: Ectopic Expression Of Stable Cdc6 Inhibits Meiosis Resumptionmentioning
confidence: 99%
“…Cdc6 and Orc6 are the only DNA replication protein missing in the oocytes of flies, frogs, and mice whose translation during meiotic maturation is necessary and sufficient to confer DNA replication competence before fertilization (Lemaitre, Bocquet, & Mechali, 2002; Lemaitre et al, 2004; Murai, Stein, Buffone, Yamashita, & Schultz, 2010; Whitmire, Khan, & Coue, 2002). In addition to their role in origin licensing, Cdc6 also behaves as a Cdk1 inhibitor that regulates entry into and progression through mitosis by limiting the level of Cdk1 activity (El Dika et al, 2014). Fertilization triggers formation of two pronuclei, followed by nuclear DNA replication, and then mitosis, all of which happens in the absence of DNA transcription.…”
Section: The First Mitotic Cell Division Is Universalmentioning
confidence: 99%